(untitled) (LACCEI, 2024)
High Andean wetlands fulfill ecological and socioeconomic functions, such as water regulation, sustaining a diversity of fauna and flora, providing forage and recreational spaces. For this reason, they are considered fragile ecosystems due to their ecosystem functions, the diversity of species they harbor, and their dependence on water. Therefore, due to the instability of climatic conditions, the present research aims to evaluate the influence of climate variability on the spatiotemporal dynamics of wetlands during the period 1988-2022, for which climatic data and Landsat 5, Landsat 8 and Sentinel 2. The spectral classification of wetlands was carried out using NDVI within the range 0.436 to 1. The trend of climatic variables was determined using the Mann Kendall test, and the influence of climatic variables was determined using ANOVA and Kruskall Wallis. The result indicates that only cumulative precipitation influences wetland spatiotemporal dynamics (P 0.05, R2=0.4838, ε2 = 0.431) with a moderate effect and 48.38% dependence on precipitation.